Online Study during Covid’ 19: What Students Like and Dislike in Online Courses - Bari, Moncef; Minh, Nguyen Thi Ai (International Journal of Learning and Development, 2024)
This article presents the results of a research about the students’ likes and dislikes in online courses. The project used surveys to the students of the Dalat University in Vietnam conducted during the fall term of 2021. After analyzing the sample of 708 students, it appears that the main findings are somehow close to many studies conducted at the same time approximately. Mainly, the students like the flexibility of asynchronous courses and the availability of the learning material at any time. They dislike the lack of interaction with the teachers and their classmates. As for online asynchronous courses, students like the possibility of interacting with teachers and classmates (in the case of interactive courses) and the clarity of the schedule. In all cases, the quality of the Internet connection and the power supply appear as a sine qua non condition to any satisfaction supporting any distance studies. Some students have also noted health problems inherent to too long periods sitting in front of screens. This aspect is particularly critical for those who do not have computers and who are forced to work on their smartphones.